Nematodes from galls on Myrtaceae. III. Fergusobia from flower bud and stigma galls on Eucalyptus, with descriptions of four new species - Davies, Kerrie; Giblin-Davis, Robin; Ye, Weimin; Taylor, Gary; Thomas, Kelley (Zootaxa, 2012)
Four new species of Fergusobia from flower bud galls and a stigma gall on Eucalyptus spp. in Australia are described. Fer-gusobia eugenioidae Davies n. sp. is characterised by having an arcuate, open C or C-shaped parthenogenetic female witha conoid tail, an arcuate to open C-shaped infective female with a hooked tail region and a broadly rounded tail tip, andarcuate or open C-shaped males with angular spicules and short bursa. Fergusobia fasciculosae Davies n. sp. is character-ised by the combination of an arcuate parthenogenetic female with a short, broadly conoid tail, an open C-shaped infectivefemale with a hemispherical tail tip, and J-shaped males with angular spicules and short peloderan bursa. This is the firstFergusobia/Fergusonina association to be described from flower stigma galls. Fergusobia juliae Davies n. sp. is character-ised by the combination of an arcuate to C-shaped parthenogenetic female with a short, broadly conoid tail, a J-shaped in-fective female with a hooked tail region, a cuticular plate around the vulva, and a broadly rounded tail tip, and J-shapedmales with angular spicules and short peloderan bursa. Fergusobia morrisae Davies n. sp. has a C-shaped parthenogeneticfemale with a narrowly conoid tail, an arcuate or J-shaped infective female with most curvature behind the vulva and a shorttail with an almost hemispherical tip, and arcuate or J-shaped males with strongly sclerotised, angular spicules and a longpeloderan bursa. Other known similar forms of Fergusobia/Fergusonina flower bud galls from Eucalyptus spp. are outlinedand the larval shield morphology of their associated mutualistic fly species is discussed where known. An inventory of allknown Fergusobia/Fergusonina associations from flower bud galls from Eucalyptus spp. is presented. Molecular analysisof Fergusobia nematodes was inferred from DNA sequencing of 28S rDNA D2/D3 domains and a portion of mitochondrial DNA cytochrome oxidase subunit I (mtCOI). Possible evolutionary relationships are discussed.